Mental Health Policy Adoption as a Seminal Event: A Response to Recent Commentaries - Gordon C Shen (Kerman University of Medical Sciences, 2015)
The leadership for mental health is not commensurate with the burden of mental, neurological, and substance (MNS) use disorders nationally or internationally. This is a sentiment I share with Prof. Jenkins (1) and Ms. Lee (2). With that said, I would like to make two clarifications about my study and two concomitant acknowledgements about its limitations (3). First, I conceptualized national mental health policy adoption as an isolated event. Policy adoption is one - albeit pivotal - node embedded in a ratification process. Second, I focused solely on external actors' influence on policy adoption. Politics and policy are intertwined, and there are certainly actors situated inside, as well as outside, each country who are engaged with mental health policy-making, but they were not addressed by my study. I will elaborate on what I set out to do before giving pointed responses to their comments.